ANALISIS PENGGUNAAN MEDIA MIND MAPPING PAI DI SDIT UMMATAN WAHIDAH - Puspita Aryani; Ramaita Ramaita; Rahma Sangkut; Siswanto Siswanto (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research is based on the fact that SDIT Ummatan Wahidah in Islamic Religious Education subjects has implemented a mind mapping model. The role of educators in the learning process is very large, because the task of educators is not just to understand and transfer knowledge. However, an educator also needs to master the skills to design learning models, and be able to apply learning models that are commensurate with the level of students' understanding. Because, one of the obstacles for students is the slow activity in understanding the material, so that students' weaknesses are not correctly interpreting the information that has been obtained. The aim of the research is to determine the use of mind mapping media in learning Islamic Religious Education and find out the advantages and disadvantages of applying the mind mapping model in learning Islamic Religious Education at SDIT Ummatan Wahidah. The type of research used is field research and uses a descriptive approach. The subjects in this research were the Principal, Teachers and Students at SD IT Ummatan Wahidah. The data collection techniques used were observation, interviews and documentation. Meanwhile, data analysis techniques use data reduction, data display (data presentation) and conclusion drawing and varification (drawing conclusions and verifying). The results of the research show that in using mind mapping media in learning Islamic Religious Education at SDIT Ummatan Wahidah, students are formed into groups. Students are invited to be creative. After that, students can attach the image or photo to the mind mapping sheet that has been created. Next, one representative from each group was given the opportunity to present the results. The advantages of the mind mapping model are that it sharpens students' creativity, trains students to think critically, trains self-confidence, with students daring to raise their hands when giving opinions, when discussing and asking questions, training them in making interesting and unique concept maps, making it easier to remember information, and create an independent personality. Meanwhile, the disadvantage of the mind mapping model is that it can only include important points, so it cannot include material in detail and in detail, it lacks references for examples of pictures, charts, symbols and symbols, for students who read slowly it will be a little difficult to find. the main ideas or notions in the material, and the results of mind mapping are only understood by the students who created them, unless the results have been explained by the creators to other students.